Patterns and progress of Malaysia’s amphibian research in the 21st century - Kin Onn, Chan; Norhayati, Ahmad; Shahrul, Anuar; Yong Min, Pui; Das, Indraneil (National University of Singapore, 2022)
We review the status, patterns, and progress of Malaysia’s amphibian research in the 21st century (2000–2021) with the main goal of identifying areas for improvement that can help focus and prioritise future research initiatives. Between the period of January 2000–September 2021, we found 280 publications that can be broadly grouped into five categories: 1) Checklists and Biodiversity; 2) New Species, Taxonomy, and Identification; 3) Ecology and Natural History; 4) Evolution and Phylogenetics; 5) Conservation. An average of 12.7 papers were published per year and although the number of papers fluctuated, there was an overall positive trend towards higher research output. The majority of research was from the Checklists and Biodiversity (34%; 95 papers) and New Species, Taxonomy, and Identification (35%; 97 papers) categories, followed by Ecology and Natural History (21%; 59 papers), Evolution and Phylogenetics (9%; 25 papers), and Conservation (1%; four papers). Amphibian research was conducted most frequently in the Bornean states of Sarawak (45 papers) and Sabah (34 papers) and most infrequently in the states of Malacca (one paper), Negeri Sembilan (two papers), Selangor/Kuala Lumpur (two papers), Perlis (two papers), and Kelantan (three papers). Despite being a megadiverse country and a biodiversity hotspot, only four conservation studies were published over the last two decades, highlighting the urgent need for more conservation-focused research.